Building Superior Human Resources To Support Community Based Tourism - Faozen; Anggraini , Cristian Rizqi; Adawiyah , Putri Robiatul (Journal of Applied Management and Business, 2025)
This research aims to examine the key factors influencing the success of community based tourism management in Jember Regency. The study focuses on four main aspects, education and training, stakeholder collaboration, tourism environment management, and digital literacy as determinants of effective community-based tourism governance. Using a multiple linear regression approach, data were collected from 120 respondents comprising local residents, tourism business actors, and related stakeholders. The findings reveal that education and training (X1), management of the tourism environment (X3), and digital literacy (X4) significantly and positively affect the success of community-based tourism management. Conversely, collaboration among stakeholders (X2) does not show a significant impact within this model. Overall, the four independent variables collectively exert a significant influence on the dependent variable, with an R² value of 0.661, indicating that 66.1% of the variation in tourism management success can be explained by these factors. The results emphasize that enhancing human resource capacity through education and training, improving environmental management practices, and strengthening digital literacy are crucial strategies for achieving sustainable community-based tourism. Practically, this study underscores the importance of government and institutional support in implementing policies and programs aimed at empowering local communities to actively manage and develop tourism destinations.